Goal‐Striving Stress and Incident Cardiovascular Disease in Blacks: The Jackson Heart Study - LáShauntá M. Glover; Loretta R. Cain‐Shields; Tanya M. Spruill; Emily C. O'Brien; Sharrelle Barber; Laura Loehr; Mario Sims (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background Goal‐striving stress (GSS), the stress from striving for goals, is associated with poor health. Less is known about its association with cardiovascular disease (CVD). Methods and Results We used data from the JHS (Jackson Heart Study), a study of CVD among blacks (21–95 years old) from 2000 to 2015. Participants free of CVD at baseline (2000–2004) were included in this analysis (n=4648). GSS was examined in categories (low, moderate, high) and in SD units. Incident CVD was defined as fatal or nonfatal stroke, coronary heart disease (CHD), and/or heart failure. We used Cox proportional hazards regression to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) of incident CVD by levels of GSS, adjusting for demographics, socioeconomic status, health behaviors, risk factors, and perceived stress. The distribution of GSS categories was as follows: 40.77% low, 33.97% moderate, and 25.26% high. Over an average of 12 years, there were 140 incident stroke events, 164 CHD events, and 194 heart failure events. After full adjustment, high (versus low) GSS was associated with a lower risk of stroke (HR, 0.38; 95% CI, 0.17–0.83) and a higher risk of CHD (HR, 1.91; 95% CI, 1.10–3.33) among women. A 1‐standard deviation unit increase in GSS was associated with a 31% increased risk of CHD (HR, 1.31; 95% CI, 1.10–1.56) among women. Conclusions Higher GSS may be a risk factor for developing CHD among women; however, it appears to be protective of stroke among women. These analyses should be replicated in other samples of black individuals.